The PATH to PPE Mastery - Programme for Assessment and Training in HCID (High Consequence Infectious Diseases) PPE (Personal Protective Equipment), Mastery - Callum P. Mutch; James Tiernan; Oliver Koch; Bozena Poller (Elsevier, 2023)
Summary: Background: High Consequence Infectious Diseases (HCIDs), have the potential to cause pandemics and require particular focus for preparedness due to their high mortality rates. The application of Personal Protective Equipment (PPE) for HCIDs is complex and carries significant risk of Health Care Worker (HCW) contamination if done incorrectly. Previous reviews have reported a lack of information on the nature of training provided and the ideal timing of repeat training to best retain skills. Simulation Based Mastery Learning (SBML) is a methodology for skill acquisition which encompasses deliberate practice and repeated assessment until the learner achieves a pre-set Mastery standard. SBML has been demonstrated to improve competence, skill retention and patient outcomes in other clinical procedures. SBML has not been previously studied or utilised in HCID PPE training. Aim: We aimed to increase the likelihood of safe clinical practice by evidencing that Lothian modified SBML for PPE effectively prepares our priority learners. Methods: A quasi-experimental within group post-test design was used. Learners undertook a modified SBML programme which included two-hour asynchronous and two-hour synchronous components. Findings: 11 learners (10 infectious diseases registrars and 1 infectious diseases consultant) were enrolled in the programme with 8 completing all stages, all of whom achieved the Mastery passing standard. The resources were highly rated by learners with the exemplar videos of skills highlighted as particularly useful. Self-assessed preparedness for each skill increased following pre-learning and synchronous sessions. Conclusion: Modified SBML can be used as an effective methodology for the training and assessment of HCWs in the donning and doffing of HCID PPE.